2017
DOI: 10.1038/srep41297
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of spatiotemporal patterns of Ras isoform expression during development

Abstract: Ras proteins are important signalling hubs frequently dysregulated in cancer and in a group of developmental disorders called Rasopathies. Three Ras genes encode four proteins that differentially contribute to these phenotypes. Using quantitative real-time PCR (qRT-PCR) we have measured the gene expression profiles of each of the Ras isoforms in a panel of mouse tissues derived from a full developmental time course spanning embryogenesis through to adulthood. In most tissues and developmental stages we observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 43 publications
1
45
2
Order By: Relevance
“…While a number of factors could contribute to this variation in mutagenesis [59][60][61] , one notable difference is that Kras mRNA levels are higher in the lung compared with these other tissues, suggestive of increased transcription. In fact, the lung was found to have the second highest levels of Kras mRNA of 15 adult murine tissues analyzed, second only to the brain 35 . Kras expression in the mouse lung also correlates with strain susceptibility to urethane carcinogenesis 62,63 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…While a number of factors could contribute to this variation in mutagenesis [59][60][61] , one notable difference is that Kras mRNA levels are higher in the lung compared with these other tissues, suggestive of increased transcription. In fact, the lung was found to have the second highest levels of Kras mRNA of 15 adult murine tissues analyzed, second only to the brain 35 . Kras expression in the mouse lung also correlates with strain susceptibility to urethane carcinogenesis 62,63 .…”
Section: Discussionmentioning
confidence: 96%
“…Mutational strand asymmetry has been observed for other mutational processes 32,33 and correlated with the transcriptional status of mutated genes 34 . Kras mRNA levels determined by quantitative RT-PCR (RT-qPCR) 35 or RNA-seq 36 have been reported to be higher in the murine lung compared with the liver. In agreement, we validated the higher expression of Kras mRNA in lung compared with liver and pancreas by RT-qPCR ( Fig.…”
Section: ′ Base Nucleotidementioning
confidence: 99%
“…HRAS showed a significant noticeable trend of expression levels by decreasing exponentially from PF to SYF (p  0.05), which suggest that HRAS may have dynamic functional activities during the prehierarchical follicle development. Previous studies reported the spatial and temporal HRAS mRNA transcripts during mice development expressed in a stage development and tissue specific manner with the highest expression in the adult brain (Newlaczyl et al, 2017). Moreover, higher expression of MEK1 was observed in SWF suggesting that MEK1 may have an active role by either suppressing or promoting the development of prehierarchical follicle.…”
Section: Results and Discussion Mrna Expression Levels Of Erk Hras Amentioning
confidence: 90%
“…Quantification of spatiotemporal patterns of Ras isoforms expression during development showed a relative contribution of KRas4B > > NRas ≥ KRas4A > HRas to the total Ras expression with KRas4B typically representing 60-99 % of all Ras transcripts. KRas4A was the most dynamically regulated Ras isoform with significant up-regulation of the expression observed in stomach, intestine, kidney and heart [21]. The functional divergence may be explained, at least partially, by different membrane compartmentalization of the Ras isoforms [22].…”
Section: Dissimilar Functions Of the Same Protein Isoformsmentioning
confidence: 98%